A photocurable dyeing resin and its preparation method and application

By using acrylate modified polysiloxane and high-efficiency photoinitiator in dental resin materials, the double bond conversion rate and the water absorption rate are improved, and the problem of insufficient color stability of dental resin materials is solved, achieving excellent stain resistance and color stability.

CN119732844APending Publication Date: 2025-04-01AIDITE (QINHUANGDAO) TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411945659.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

After long-term exposure of dental resin materials in the oral region, their color stability is insufficient and they are easily affected by exogenous colorants, resulting in color changes, affecting their aesthetic appearance and the patient's mental health.

Method used

Acrylate modified polysiloxane is used as the resin matrix, combining multifunctional acrylate and an efficient photoinitiator to prepare a photocuring dyeing resin with excellent dye resistance by increasing the double bond conversion rate and reducing water absorption.

Benefits of technology

When facing common dyeing sources such as green tea, cola, red wine and coffee, this resin material exhibits excellent stain resistance, good color stability, and is not easily colored by exogenous, meeting the high requirements for anti-dyeing in dental materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005213575750000101
    Figure BDA0005213575750000101
  • Figure BDA0005213575750000111
    Figure BDA0005213575750000111
Patent Text Reader

Abstract

The present invention provides a photocurable dyeing resin and a preparation method and application thereof. The raw materials for preparing the photocurable dyeing resin include the following components by weight: 10 to 60 parts of acrylate-modified polysiloxane, 20 to 70 parts of multifunctional acrylate, 10 to 50 parts of monofunctional acrylate, 0.5 to 6 parts of photoinitiator, 0 to 10 parts of filler, and 0 to 5 parts of additive. The acrylate-modified polysiloxane is synthesized by reacting a diacrylate compound with an amino-containing siloxane compound. The photocurable dyeing resin of the present invention has excellent staining resistance, good color stability, and is not easily colored by external sources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oral materials and relates to a light-curing dyeing resin and a preparation method and application thereof. Background Art

[0002] The rapid development of oral material research has made oral restoration materials no longer emphasize only functional restoration, but the durability of materials is the focus, and the color of materials is increasingly valued by clinicians and patients. As people's demand for dental beauty continues to increase, dyed resins can provide restorations with a more natural and realistic appearance, making them occupy a place in the dental material market. The use of dyed resins can produce restorations that match the color of surrounding teeth, which can achieve very good aesthetic effects and improve patients' self-confidence. Despite providing satisfactory strength and a highly aesthetic appearance, the color stability of resin materials after long-term intraoral exposure remains a problem.

[0003] In the oral environment, resin materials may come into contact with a variety of staining substances, including food (such as colored beverages such as coffee, tea, and red wine), tobacco, and oral bacterial metabolites. These staining substances can enter the interior of the resin material through adsorption, penetration, and other mechanisms, causing the color of the resin-based restoration to change. Staining problems not only affect the patient's oral aesthetics, but may also cause dissatisfaction with the restoration effect, and may even affect the patient's mental health and social life. Therefore, studying the staining resistance of dental resin materials has important clinical and social significance.

[0004] The causes of discoloration of resin materials can be divided into internal and external factors. Internal factors depend on the chemical composition of the material itself, such as the resin matrix, filler loading and particle size, photoinitiator type and other factors. External factors are mainly the adsorption of exogenous colorants (from smoking, diet, etc.), which depends on the environment to which the restoration is exposed. Water absorption and dissolution can also have a negative impact on the physical and chemical properties and aesthetic characteristics of composite resins, such as changes in flexural strength and color. At present, many studies at home and abroad have proved that cola, coffee, tea, red wine, etc. have exogenous staining effects on composite resins.

[0005] Therefore, how to prepare a light-cured dental staining resin with excellent stain resistance is the research focus in this field. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention aims to provide a photocurable dyeing resin and a preparation method and application thereof.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In one aspect, the present invention provides a photocurable dyeing resin, wherein the raw materials for preparing the photocurable dyeing resin include the following components in parts by weight:

[0009] 10-60 parts of acrylate-modified polysiloxane, 20-70 parts of multifunctional acrylate, 10-50 parts of monofunctional acrylate, 0.5-6 parts of photoinitiator, 0-10 parts of filler and 0-5 parts of additive.

[0010] The light-curable dyeing resin of the present invention has excellent dyeing resistance, good color stability, and is not easily colored by external sources.

[0011] The water absorption rate and double bond conversion rate of the resin matrix have a certain influence on the color stability of the composite resin. Low water absorption rate and high double bond conversion rate promote color change. The water absorption process of the composite resin mainly occurs in the resin matrix, so the water absorption rate of the resin matrix can better reflect the water absorption characteristics of the composite resin. Therefore, a hydrophobic resin matrix is ​​selected, and the composite resin material after light curing has a lower water absorption rate. Polysiloxane has good heat resistance, cold resistance, weather resistance and chemical stability, good water resistance, oil resistance and stain resistance, and can effectively prevent the adhesion and penetration of dyeing substances. By modifying polysiloxane with acrylate, the siloxane segment is introduced into the light-curing resin system, thereby reducing the water absorption rate of the light-curing composite resin.

[0012] The double bond conversion rate is positively correlated with the degree of resin polymerization. A low double bond conversion rate means that there are more unreacted monomers in the resin, which can promote the material's absorption of dyes. In order to improve the double bond conversion rate, on the one hand, multifunctional acrylate monomers, especially trifunctional acrylate polymerization monomers, are selected, which have higher polymerization activity and higher crosslinking density; on the other hand, (bis)acylphosphine oxide initiators are selected as photoinitiators, whose initiation activity and initiation efficiency are higher than those of the commonly used photoinitiator camphorquinone.

[0013] Therefore, by selecting a suitable resin matrix and photoinitiator and a corresponding suitable ratio, the purpose of increasing the double bond conversion rate of the monomer and reducing the water absorption rate of the composite resin can be achieved, thereby obtaining a photocurable resin material with excellent staining resistance.

[0014] In the raw materials for preparing the light-curable dyed resin of the present invention, the amount of the acrylate-modified polysiloxane is 10 parts, 13 parts, 15 parts, 18 parts, 20 parts, 25 parts, 28 parts, 30 parts, 35 parts, 38 parts, 40 parts, 45 parts, 48 ​​parts, 50 parts, 55 parts, 58 parts or 60 parts.

[0015] In the raw materials for preparing the light-curable dyeing resin of the present invention, the amount of the multifunctional acrylate is 20 parts, 25 parts, 28 parts, 30 parts, 35 parts, 38 parts, 40 parts, 45 parts, 48 ​​parts, 50 parts, 55 parts, 58 parts, 60 parts, 63 parts, 65 parts, 68 parts or 70 parts.

[0016] In the raw materials for preparing the light-curable dyeing resin of the present invention, the amount of the monofunctional acrylate is 10 parts, 14 parts, 15 parts, 18 parts, 20 parts, 25 parts, 28 parts, 30 parts, 35 parts, 38 parts, 40 parts, 45 parts, 48 ​​parts or 50 parts.

[0017] In the raw materials for preparing the light-curable dyed resin of the present invention, the amount of the photoinitiator can be 0.5 parts, 0.8 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts or 6 parts.

[0018] In the raw materials for preparing the light-curable dyed resin of the present invention, the amount of the filler can be 0 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts.

[0019] In the raw materials for preparing the light-curable dyeing resin of the present invention, the amount of the additive can be 0 parts, 1 parts, 2 parts, 3 parts, 4 parts or 5 parts.

[0020] In the present invention, the acrylate-modified polysiloxane is synthesized by reacting a diacrylate compound with an amino-containing siloxane compound.

[0021] Preferably, the preparation method of the acrylate-modified polysiloxane comprises the following steps:

[0022] The diacrylate monomer, the amino-containing siloxane compound and the polymerization inhibitor are mixed and reacted to obtain an acrylate-modified polysiloxane.

[0023] Preferably, the diacrylate monomer is selected from any one of ditrimethylolpropane acrylate, urethane dimethacrylate or ethoxylated bisphenol A dimethacrylate, or a combination of at least two thereof.

[0024] Preferably, the amino-containing silicone compound is selected from aminopropyl-terminated polydimethylsiloxane.

[0025] Preferably, the aminopropyl-terminated polydimethylsiloxane has a molecular weight of 250-2000 g / mol; for example, the molecular weight is 250, 500, 1000 or 2000 g / mol.

[0026] Preferably, the polymerization inhibitor is selected from any one of hydroquinone, p-hydroxyanisole, polymerization inhibitor-702 or polymerization inhibitor 705, or a combination of at least two thereof.

[0027] Preferably, the reaction molar ratio of the acrylate groups in the diacrylate monomer to the amino groups in the amino-containing siloxane compound is 2.5 to 4:1, for example, 2.5:1, 2.8:1, 3:1, 3.5:1, 3.8:1 or 4:1.

[0028] Preferably, the reaction temperature is 20°C to 80°C, for example 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, and the reaction time is 2 to 6 hours, for example 2 hours, 3 hours, 4 hours, 5 hours or 6 hours.

[0029] In the present invention, the multifunctional acrylate refers to an acrylate with two or more functions. Preferably, the multifunctional acrylate includes one or a combination of at least two of pentaerythritol tetraacrylate, ditrimethylolpropane tetraacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, ditrimethylolpropane acrylate, urethane dimethacrylate or ethoxylated bisphenol A dimethacrylate.

[0030] Preferably, the monofunctional acrylate includes one or a combination of at least two of methyl methacrylate, tetrahydrofuranyl acrylate, allyl methacrylate, isobornyl methacrylate or cyclotrimethylolpropane formal acrylate.

[0031] Preferably, the photoinitiator is a (bis)acylphosphine oxide initiator.

[0032] Preferably, the photoinitiator is selected from one or a combination of at least two of bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoylethoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide or 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide.

[0033] Preferably, the filler is selected from one or a combination of at least two of zirconium oxide, fumed silica, nano titanium dioxide, strontium glass powder or barium glass powder, preferably nano titanium dioxide and / or fumed silica.

[0034] Preferably, the additive comprises one or a combination of at least two of a stabilizer, an antioxidant inhibitor, a colorant or an anti-aging agent.

[0035] In another aspect, the present invention provides a method for preparing the light-curable dyeing resin as described above, the method comprising the following steps:

[0036] Acrylate modified polysiloxane, multifunctional acrylate, monofunctional acrylate, photoinitiator, filler and additive are mixed and stirred to obtain light-curing dyeing resin.

[0037] Preferably, the stirring speed is 250-800 r / min (for example, 250 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min or 800 r / min), the stirring time is 2-6 h (for example, 2 h, 3 h, 4 h, 5 h or 6 h), and the stirring is carried out at a temperature of 20-80 ° C (for example, 20 ° C, 30 ° C, 40 ° C, 60 ° C, 70 ° C or 80 ° C).

[0038] Preferably, the mixing includes: firstly mixing and stirring the acrylate-modified polysiloxane, multifunctional acrylate and monofunctional acrylate evenly, then dissolving the photoinitiator and additives in the mixed resin matrix, and finally adding the filler and mixing and stirring evenly.

[0039] In another aspect, the present invention provides use of the above-mentioned light-curable dyed resin in a dental composite resin restoration.

[0040] The light-curable dyeing resin of the present invention is cured under an ultraviolet-visible light source to be applied to the color adjustment of dental composite resin restorations.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] The light-curable dyeing resin of the present invention has excellent dyeing resistance, good color stability, and is not easily colored by external sources. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0044] Example 1

[0045] Preparation of acrylate-modified polysiloxane: 1357.62 g of 1,6-hexanediol diacrylate and 372.76 g of disiloxane diamine were mixed and put into a stirring kettle, 0.17 g of polymerization inhibitor p-hydroxyanisole was added, the temperature was raised to 60° C. and kept for reaction for 3 hours, and the acrylate-modified polysiloxane was obtained by cooling to room temperature.

[0046] 300 g of acrylate-modified polysiloxane, 200 g of trimethylolpropane triacrylate, 200 g of ethoxylated bisphenol A dimethacrylate and 200 g of isobornyl methacrylate were added to a stirring kettle respectively, the stirring kettle was placed in a 50°C water bath, and an electric stirrer was used to stir at 200 r / min for 1 hour and 400 r / min for 2 hours to form a homogeneous resin system; 30 g of 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide was added to the stirring kettle, and the electric stirrer was stirred at 400 r / min for 2 hours until the solid particles were completely dissolved; 70 g of fumed silica was weighed and added to the stirring kettle, and the electric stirrer was stirred at 300 r / min for 4 hours until a homogeneous system was formed to obtain a photocurable composite resin.

[0047] Example 2

[0048] The preparation of acrylate-modified polysiloxane is the same as that in Example 1.

[0049] 100 g of acrylate-modified polysiloxane, 300 g of trimethylolpropane triacrylate, 400 g of ethoxylated bisphenol A dimethacrylate and 170 g of isobornyl methacrylate were added to a stirring kettle respectively, the stirring kettle was placed in a 50°C water bath, and an electric stirrer was used to stir at 200 r / min for 1 hour and at 400 r / min for 2 hours to form a homogeneous resin system; 5 g of 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide was added to the stirring kettle, and the electric stirrer was stirred at 400 r / min for 2 hours until the solid particles were completely dissolved; 25 g of fumed silica was weighed and added to the stirring kettle, and the electric stirrer was stirred at 300 r / min for 4 hours until a homogeneous system was formed to obtain a photocurable composite resin.

[0050] Example 3

[0051] The preparation of acrylate-modified polysiloxane is the same as that in Example 1.

[0052] 600 g of acrylate-modified polysiloxane, 100 g of trimethylolpropane triacrylate, 100 g of ethoxylated bisphenol A dimethacrylate and 140 g of tetrahydrofuran acrylate were added into a stirring kettle respectively, the stirring kettle was placed in a 50°C water bath, an electric stirrer was used to stir at 200 r / min for 1 hour and at 400 r / min for 2 hours to form a homogeneous resin system; 60 g of 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide was added into the stirring kettle, the electric stirrer was stirred at 400 r / min for 2 hours, the solid particles were completely dissolved, and a photocurable composite resin was obtained.

[0053] Example 4

[0054] The preparation of acrylate-modified polysiloxane is the same as that in Example 1.

[0055] 180g of acrylate-modified polysiloxane, 100g of trimethylolpropane triacrylate, 100g of ethyl formate dimethacrylate and 500g of isobornyl methacrylate were added to a stirring kettle respectively, the stirring kettle was placed in a 50°C water bath, and an electric stirrer was used to stir at 200r / min for 1 hour and 400r / min for 2 hours to form a homogeneous resin system; 20g of 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide was added to the stirring kettle, and the electric stirrer was stirred at 400r / min for 2 hours until the solid particles were completely dissolved; 100g of fumed silica was weighed and added to the stirring kettle, and the electric stirrer was stirred at 300r / min for 4 hours until a homogeneous system was formed to obtain a photocurable composite resin.

[0056] Example 5

[0057] The preparation of acrylate-modified polysiloxane is the same as that in Example 1.

[0058] 400 g of acrylate-modified polysiloxane, 200 g of trimethylolpropane triacrylate, 180 g of ethyl formate dimethacrylate and 180 g of isobornyl methacrylate were added to a stirring kettle respectively, the stirring kettle was placed in a 50°C water bath, and an electric stirrer was used to stir at 200 r / min for 1 hour and at 400 r / min for 2 hours to form a homogeneous resin system; 10 g of 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide was added to the stirring kettle, and the electric stirrer was stirred at 400 r / min for 2 hours until the solid particles were completely dissolved; 30 g of fumed silica was weighed and added to the stirring kettle, and the electric stirrer was stirred at 300 r / min for 4 hours until a homogeneous system was formed to obtain a photocurable composite resin.

[0059] Example 6

[0060] The preparation of acrylate-modified polysiloxane is the same as that in Example 1.

[0061] 500 g of acrylate-modified polysiloxane, 50 g of trimethylolpropane triacrylate, 50 g of ethyl formate dimethacrylate and 350 g of isobornyl methacrylate were added to a stirring kettle respectively, the stirring kettle was placed in a 50°C water bath, and an electric stirrer was used to stir at 200 r / min for 1 hour and at 400 r / min for 2 hours to form a homogeneous resin system; 40 g of 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide was added to the stirring kettle, and the electric stirrer was stirred at 400 r / min for 2 hours until the solid particles were completely dissolved; 10 g of fumed silica was weighed and added to the stirring kettle, and the electric stirrer was stirred at 300 r / min for 4 hours until a homogeneous system was formed to obtain a photocurable composite resin.

[0062] Comparative Example 1

[0063] 300 g of pentaerythritol triacrylate, 200 g of trimethylolpropane triacrylate, 200 g of ethoxylated bisphenol A dimethacrylate and 200 g of isobornyl methacrylate were added to a stirring kettle respectively, the stirring kettle was placed in a 50°C water bath, and an electric stirrer was used to stir at 200 r / min for 1 hour and 400 r / min for 2 hours to form a homogeneous resin system; 30 g of 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide was added to the stirring kettle, and the electric stirrer was stirred at 400 r / min for 2 hours until the solid particles were completely dissolved; 70 g of fumed silica was weighed and added to the stirring kettle, and the electric stirrer was stirred at 300 r / min for 4 hours until a homogeneous system was formed to obtain a photocurable composite resin.

[0064] Comparative Example 2

[0065] 300 g of trimethylolpropane triacrylate, 300 g of ethoxylated bisphenol A dimethacrylate and 300 g of isobornyl methacrylate were added to a stirring kettle respectively, the stirring kettle was placed in a 50°C water bath, and an electric stirrer was used to stir at 200 r / min for 1 hour and 400 r / min for 2 hours to form a homogeneous resin system; 30 g of 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide was added to the stirring kettle, and the electric stirrer was stirred at 400 r / min for 2 hours until the solid particles were completely dissolved; 70 g of fumed silica was weighed and added to the stirring kettle, and the electric stirrer was stirred at 300 r / min for 4 hours until a homogeneous system was formed to obtain a photocurable composite resin.

[0066] The following performance tests were performed on the composite resins prepared in the examples and comparative examples:

[0067] (1) Bending strength test

[0068] The test was carried out according to the YY 1042-2023 standard. Specifically, the sample was filled into a mold with a width of (2±0.1) mm × a thickness of (2±0.1) mm × a length of (25±0.1) mm, and irradiated with a handheld dental light curing lamp, divided into three areas: upper, middle and lower. Each area was irradiated for 40 seconds, and then demolded. The above steps were repeated to prepare 5 specimens, and then the surface was polished with 2000 mesh sandpaper wet grinding. A three-point bending test was carried out using a tensile testing machine with a span of 20 mm and a loading speed of (0.75±0.25) mm / min. The average value of the 5 specimens was used for evaluation.

[0069] (2) Shear bond strength

[0070] Refer to the YY 0518-2009 standard and use dyed resin instead of adhesive for testing. Use composite resin material, polish the surface with sandpaper, clean the residual powder on the surface with running water and blow dry, use 5% hydrofluoric acid to etch, and use silane coupling agent to siliconize the surface. Apply the dyed resin sample to the small piece of the bonding part, place the small column of composite resin material on the small hole, press it with a heavy hammer, and cure it with a light curing lamp. The shear strength test is carried out on a universal mechanical testing machine. The shear test equipment is placed between the two parallel tables of the testing machine. The upper table moves the shear knife downward to apply shearing action to the sample. When the upper table contacts the shear knife, it should be ensured that there is no impact on the sample. The shear speed is (0.75±0.30)mm / min. The average value of 5 samples is evaluated.

[0071] Calculation results:

[0072]

[0073] Where:

[0074] F-shear bond strength, MPa;

[0075] P-maximum applied load, N;

[0076] d-bonding diameter, mm.

[0077] (3) Anti-staining test

[0078] 1. Sample Preparation

[0079] Three samples with a thickness of 1 mm and a diameter of 15 mm were made for each resin material. Production process: A polyester film was placed on a glass sheet, and then a mold was placed on it. The mold was filled with resin material, and the polyester film and glass sheet were compressed on top of the material to remove excess material to obtain a smooth surface for color measurement. Each sample was irradiated and cured using a handheld dental light curing lamp, and then demolded to obtain the sample, and the surface was polished with 2000-grit sandpaper, cleaned, and air-dried.

[0080] 2. Testing process

[0081] The samples were packed in ziplock bags marked with "green tea", "cola", "red wine" and "coffee". 30 mL of green tea, cola, red wine and coffee were injected into the corresponding ziplock bags and soaked at 37°C for 24 hours. The samples were taken out and rinsed under running water. The moisture on the surface of the samples was wiped dry with absorbent paper. The L, a and b values ​​of the samples were tested with a spectrophotometer, and the average values ​​were taken to calculate the color difference of the samples.

[0082] The formula for calculating color difference is as follows:

[0083] △E=[(△L*) 2 +(△a*) 2 +(△b*) 2 ] 1 / 2

[0084] Among them, △E is the color difference value, the unit is NBS.

[0085] The performance test results are shown in Table 3.

[0086] Table 3

[0087]

[0088] Through a series of test results, it can be clearly known that the resin material prepared by the present invention exhibits excellent stain resistance on the basis of fully ensuring that the material itself has good bending strength and the bonding strength between it and the composite resin material is also in a stable and reliable state. This stain resistance is excellent in a variety of staining tests simulating oral environments. In the test of common beverage environment, the color difference values ​​(△E) of Examples 1-6 after soaking in easily stained liquids such as green tea, cola and coffee for 24 hours are lower than the color difference values ​​of Comparative Examples 1-2, and △E <1.5. This data fully demonstrates the excellent resistance of the resin material when facing these common staining sources. It is more noteworthy that even in the extremely easy-to-stain red wine environment, the color difference values ​​of Examples 1-6 after soaking for 24 hours are all lower than 3.0, which is much smaller than the color difference value of Comparative Examples 1-2 (△E>10), further highlighting the excellent stain resistance of the resin material prepared by the present invention.

[0089] In summary, this excellent anti-staining property enables the resin material to effectively resist the occurrence of exogenous staining, thereby providing an extremely strong guarantee for its long-term stable use in the field of dental material applications, and can better meet the high requirements for material anti-staining properties in dental restorations.

[0090] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the light-curable dyeing resin and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A photocurable dyeing resin, characterized in that: The raw materials for preparing the light-curable dyeing resin include the following components in parts by weight: 10-60 parts of acrylate-modified polysiloxane, 20-70 parts of multifunctional acrylate, 10-50 parts of monofunctional acrylate, 0.5-6 parts of photoinitiator, 0-10 parts of filler, 0-5 parts of additive; The acrylate-modified polysiloxane is synthesized by reacting a diacrylate compound with an amino-containing siloxane compound.

2. The light-curable dyeing resin according to claim 1, characterized in that: The preparation method of the acrylate-modified polysiloxane comprises the following steps: The diacrylate monomer, the amino-containing siloxane compound and the polymerization inhibitor are mixed and reacted to obtain acrylate-modified polysiloxane; Preferably, the diacrylate monomer is selected from any one or a combination of at least two of ditrimethylolpropane acrylate, urethane dimethacrylate or ethoxylated bisphenol A dimethacrylate; Preferably, the amino-containing silicone compound is selected from aminopropyl-terminated polydimethylsiloxane; Preferably, the molecular weight of the aminopropyl-terminated polydimethylsiloxane is 250-2000 g / mol; Preferably, the inhibitor is selected from any one of hydroquinone, p-hydroxyanisole, inhibitor-702 or inhibitor 705, or a combination of at least two thereof; Preferably, the reaction molar ratio of the acrylate group in the diacrylate monomer to the amino group in the amino-containing siloxane compound is 2.5 to 4:1; Preferably, the reaction temperature is 20° C. to 80° C., and the reaction time is 2 to 6 hours.

3. The light-curable dyeing resin according to claim 1 or 2, characterized in that: The multifunctional acrylate includes one or a combination of at least two of pentaerythritol tetraacrylate, ditrimethylolpropane tetraacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, ditrimethylolpropane acrylate, urethane dimethacrylate or ethoxylated bisphenol A dimethacrylate.

4. The light-curable dyeing resin according to any one of claims 1 to 3, characterized in that: The monofunctional acrylate includes one or a combination of at least two of methyl methacrylate, tetrahydrofuran acrylate, allyl methacrylate, isobornyl methacrylate or cyclotrimethylolpropane formal acrylate.

5. The light-curable dyeing resin according to any one of claims 1 to 4, characterized in that: The photoinitiator is any one of an acylphosphine oxide initiator or a bisacylphosphine oxide initiator or a combination of at least two thereof; Preferably, the photoinitiator is selected from one or a combination of at least two of bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoylethoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide or 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide.

6. The light-curable dyeing resin according to any one of claims 1 to 5, characterized in that: The filler is selected from one or a combination of at least two of zirconium oxide, fumed silica, nano titanium dioxide, strontium glass powder or barium glass powder, preferably nano titanium dioxide and / or fumed silica; Preferably, the additive comprises one or a combination of at least two of a stabilizer, an antioxidant inhibitor, a colorant or an anti-aging agent.

7. The method for preparing a light-curable dyed resin according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: Acrylate modified polysiloxane, multifunctional acrylate, monofunctional acrylate, photoinitiator, filler and additive are mixed and stirred to obtain light-curing dyeing resin.

8. The preparation method according to claim 7, characterized in that: The stirring speed is 250-800 r / min, the stirring time is 2-6 hours, and the stirring is carried out at a temperature of 20-80°C.

9. The preparation method according to claim 7, characterized in that: The mixing comprises: firstly mixing and stirring acrylate-modified polysiloxane, multifunctional acrylate and monofunctional acrylate uniformly to obtain a mixture; then dissolving a photoinitiator and an additive in the mixture, and finally adding a filler and mixing and stirring uniformly.

10. Use of the light-curable dyeing resin according to any one of claims 1 to 6 in dental composite resin restorations.